Le rôle d'open access dans la diffusion des résultats de la recherche scientifique : le cas de « Archeologia e Calcoloatori » - Paola Moscati (UISPP Journal)
The author aims at highlighting the relationship between the interdisciplinary research field of digital archaeology and the new trends inaugurated by the open science movement that has recently transformed the ways in which scientific knowledge is disseminated. The article starts with a brief historical background of archaeological computing and an overview of the first attempts made to design information retrieval systems. In order to illustrate the strengths and weaknesses of the open access policy, the author focuses on the case study of the scholarly Journal «Archeologia e Calcolatori» which has early joined the Open Archives Initiative in 2005, following the Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities. After summarising some key scientific aims and editorial guidelines of the Journal, which is due to celebrate its 30th anniversary next year, the paper illustrates the main technical features of its digital repository as well as data dissemination strategies. The purpose is to explore two different issues: i) a review of the technical aspects of the open access to archaeological research results (OA publishing models, legal issues and computer technologies); ii) a review of the benefits of using electronic resources to enrich the scientific documentation and disseminate interdisciplinary culture. Finally, the paper focuses on the “Virtual Museum of Archaeological Computing” – an international project jointly promoted by the Italian CNR and the Accademia Nazionale dei Lincei – in which the articles published in « Archeologia e Calcolatori » are often retrieved to illustrate the historical evolution of archaeological computing.